2022
DOI: 10.3390/sym14040814
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Polymorphisms for Lateralisation: Modelling the Genetic and Phenotypic Architectures of Multiple Functional Modules

Abstract: Recent fMRI and fTCD studies have found that functional modules for aspects of language, praxis, and visuo-spatial functioning, while typically left, left and right hemispheric respectively, frequently show atypical lateralisation. Studies with increasing numbers of modules and participants are finding increasing numbers of module combinations, which here are termed cerebral polymorphisms—qualitatively different lateral organisations of cognitive functions. Polymorphisms are more frequent in left-handers than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 398 publications
(547 reference statements)
1
10
0
Order By: Relevance
“…Across development, the maturation of lateralized functions is associated with improved visuospatial and language abilities and enhanced cognitive efficiency 71,72 . Although the precise timing of these developmental cascades remains largely unknown 14,15 , some markers of lateralization are already apparent during gestation, for instance the leftward asymmetrical folding of the Sylvian fissure 73 . At birth, intra-hemispheric white matter connectivity across the language network is reduced in favor of strong inter-hemispheric coordination 74 , an organizational property that is consistent with the presence of prominent homotopic intrinsic connectivity from 3 to 6 months of life 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across development, the maturation of lateralized functions is associated with improved visuospatial and language abilities and enhanced cognitive efficiency 71,72 . Although the precise timing of these developmental cascades remains largely unknown 14,15 , some markers of lateralization are already apparent during gestation, for instance the leftward asymmetrical folding of the Sylvian fissure 73 . At birth, intra-hemispheric white matter connectivity across the language network is reduced in favor of strong inter-hemispheric coordination 74 , an organizational property that is consistent with the presence of prominent homotopic intrinsic connectivity from 3 to 6 months of life 75 .…”
Section: Discussionmentioning
confidence: 99%
“…However, while the lateralization of brain functions and associated behaviors has fascinated neuroscientists for over a century 9,10 , the origins, mechanisms, and consequences of hemispheric specialization are still largely unknown [11][12][13][14] . In this regard, the extent to which the asymmetrical organization of discrete processes may be evident throughout the macroscale functional organization of the cortical sheet remains an open question 15 .…”
mentioning
confidence: 99%
“…Moreover, additive genetic factors explain only one quarter of the variance in human handedness, and it has been suggested that nonshared environmental factors can explain part of the remaining variance 20 , 115 (but see Refs. 116 118 ). Hence, to understand the ontogeny of functional and brain lateralization we must elucidate the interaction between endogenous and environmental factors 2 , 3 , 11 , 14 , 17 , 66 , 67 , 69 71 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the McManus DC model of handedness and language dominance [15] was one of the most influential models of handedness ontogenesis. In his contribution to the Special Issue, entitled "Cerebral Polymorphisms for Lateralisation: Modelling the Genetic and Phenotypic Architectures of Multiple Functional Modules", McManus presents an update and extension of this model with two central changes [22]. Building upon the 2014 polygenic revision of the DC model [21], McManus presents an extended polygenic DC model informed by recent studies on the genetics of handedness and, in particular, the role of cilia.…”
Section: Theoretical Articlesmentioning
confidence: 99%